Public accounting in Hungary. Situation and challenges - SIMON, JOZSEF (Journal of Education Culture and Society, 2020)
In a democratic state, citizens expect that those currently in power be obliged to justify the way they spend and manage public funds. The enforcement of accountability has seve-ral preconditions. At the same time, the accounting system constitutes one part of the public sector’s infor-mation system. Thus, studying the information system in a systematic manner is important. The information system must meet diverse needs. The present paper aims at showing those requirements.When considered in a comparative perspective, different public accountancy systems implemented internationally show different form. Every country can decide in which area and how the cash-flow approach and accrual based accounting can be used. The purpose of this paper is to verify whether and how could the usage of accrual based accounting influence the public accounting methods and the functions of public accountancy